Reinventing Performance: Digital Transformation and Intellectual Capital in Indonesia’s New Economy Sector - Febriza, Kisthy; Almurni, Siti (Taxation and Public Finance, 2025)
This study examines the influence of digitalization and intellectual capital on the financial performance of new economy companies listed on the Indonesia Stock Exchange during 2021–2023. Using a saturated sample and panel data regression analysis, the findings reveal that digitalization does not have a significant effect on financial performance, while intellectual capital shows a strong positive influence on return on assets (ROA). The originality of this research lies in its focus on Indonesia’s new economy sector, which is highly dependent on intangible assets for value creation. By integrating digital transformation concepts with the resource-based view, this study provides empirical evidence that knowledge-based capabilities play a critical role in enhancing firm performance. The results suggest that digital investment alone is insufficient without strong intellectual foundations. Practically, the study highlights the importance of continuous human capital development, efficient organizational processes, and innovation-supporting structures. From a policy perspective, the findings indicate the need for regulatory support, including incentives for intellectual capital development and the integration of ESG principles in digital business practices